Comorbidities Among Persons With Incident Psychiatric Condition - Kyle R. Fluegge PhD,MPH (Gerontology and Geriatric Medicine, 2016)
Objective: I sought to determine how medical comorbidities co-exist with incident psychiatric condition. Method: I used data from all 11 available waves (1992-2012) of the Health and Retirement Study (HRS). I identified 4,358 index participants with self-reported incident psychiatric condition. I collected comorbidity data from participants preceding, including, and succeeding that incident wave. Comorbidities assessed included high blood pressure (HBP), diabetes mellitus, cancer, lung disease, heart disease, stroke, and arthritis. Modified Poisson regression combined with log-linked binomial regression was used to estimate relative risks (RRs) of reporting a comorbidity preceding and following the incident wave. Multiple comparison testing dictated significance of RRs with p < .007. Results: For the waves preceding the index wave, the RRs of reporting all comorbidities except HBP and cancer were significantly ( p < .007) increased. For the waves following incident psychiatric condition, the risks of reporting heart disease, diabetes, and lung disease were significantly ( p < .007) increased. These results were adjusted for participant age, race, gender, other comorbidities listed, and the wave in which a comorbidity was reported. Conclusion: The bidirectional association between a psychiatric condition and medical illnesses could only be statistically confirmed for lung disease, diabetes, and heart disease. It is of interest to determine how reporting a psychiatric condition may affect the sequelae of health care use and treatment outcomes for patients with either of these comorbidities or a combination of them.